The effect of cellulose and starch on the viscoelastic and thermal properties of acid-swollen collagen paste. (April 2020) - Sobanwa, M.; Foster, T.J.; Watson, N.J.
Abstract: Collagen pastes are processed materials obtained through the swelling of minced bovine hides using acids into a fibrous swollen structure. Depending on the application, there is a need to improve the performance of these pastes in terms of rheological properties and mechanical strength of the final product. In this work, the addition of cellulose fibres and starch granules as fillers in acid swollen collagen paste was investigated. The influence of cellulose fibre length and starch granules with different amylose and amylopectin content on the viscoelastic and thermal properties of acid swollen paste were studied as a function of mixing ratio and collagen paste concentration. Addition of cellulose and starch granules resulted in an increase in the elastic modulus of the collagen paste with the starch granules having the highest impact. Addition of cellulose and starch also affected the tan δ peak of collagen paste at different collagen concentrations as a function of temperature. The micro differential scanning calorimetry (microDSC) results indicated that the denaturation temperature value of collagen was not influenced by the presence of cellulose and starch. However, upon reheating the denaturation temperature of collagen pastes wit starch granules shifted to lower temperatures. Graphical abstract: Image 1 Highlights: The effect of adding cellulose and starch to collagen pastes was studied. The addition of cellulose and starch increased the elastic modulus of the pastes. The starch had a greater effect on the viscoelastic properties of the pastes. The denaturation temperature of the pastes was not affected by the additions.